Kecenderungan Putus Sekolah Difabel Usia Pendidikan Dasar di Jember - Miftakhuddin, Miftakhuddin (INKLUSI, 2018)
This study examines the aspirations of children with disabilities in attending school and their tendency to drop out of school. This study answers the question of how disabilities influence aspirations to attend school in relation to the tendency to drop out of school. Data were collected through interviews and observations of three children with disabilities who dropped out of school and three children with disabilities who do not. Data were analysed using the techniques of data reduction, data presentation, and conclusion drawing. The results showed that the aspirations of attending school were influenced by three considerations: targets, results of risk factor analysis, and social responses. The social response shows the most dominant attention because it is often manifested by support (friendship) or obstacles (intimidation and discrimination). If the social response is positive, then the aspirations of going to school will increase, which affects the sustainability of children in school. [Penelitian ini mengkaji aspirasi anak difabel untuk bersekolah dan kecenderungannya untuk putus sekolah. Data dikumpulkan melalui wawancara dan observasi kepada tiga anak difabel yang putus sekolah, dan tiga anak difabel yang (masih) bersekolah. Data dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa aspirasi bersekolah dipengaruhi oleh tiga pertimbangan, yaitu: tujuan atau target pembelajaran, hasil analisis faktor risiko, dan respon sosial. Respon sosial menjadi faktor paling dominan karena sering diwujudkan dengan dukungan (ikatan pertemanan) maupun hambatan (intimidasi dan diskriminasi). Jika respon sosial bersifat positif, maka aspirasi bersekolah akan meningkat, yang berdampak pada keberlanjutan anak dalam bersekolah.]